2015
DOI: 10.1128/jcm.02468-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Molecular Characteristics of Mycoplasma pneumoniae Specimens Collected from the United States and China

Abstract: g Mycoplasma pneumoniae-positive clinical specimens obtained from the United States and China during the same period were studied for their molecular characteristics. We found much more diverse genotypes and a lower prevalence of macrolide resistance in the U.S. specimens. Data from the study also showed an association of the resistance with certain genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…Previous studies also indicated a type‐shift trend between P1‐1 and P1‐2 and M4‐5‐7‐2 and M3‐5‐6‐2 in terms of the most prevalent type by year . We also found a close association between MLVA type M4‐5‐7‐2 and macrolide resistance in our previous study …”
Section: Introductionsupporting
confidence: 86%
“…Previous studies also indicated a type‐shift trend between P1‐1 and P1‐2 and M4‐5‐7‐2 and M3‐5‐6‐2 in terms of the most prevalent type by year . We also found a close association between MLVA type M4‐5‐7‐2 and macrolide resistance in our previous study …”
Section: Introductionsupporting
confidence: 86%
“…A limited amount of MRMP isolates and sporadic occurrence of other genotypes could be responsible for this phenomenon, whereas opposite results were found in areas with a higher incidence of MRMP. A correlation between increasing macrolide resistance and MLVA type 4/5/7/2 had been found in Hong Kong based on four years of data during 2011-2014 (Ho et al, 2015), as well as in the specimens collected from the United States and China (Sun et al, 2017;Yan et al, 2015). In the current study, similarly, all M. pneumoniae strains with P1 type 1 or MLVA type 4/ 5/7/2 were resistant to macrolide, however, those with type 2 lineages or type 3/5/6/2 could be probably sensitive to macrolide.…”
Section: Characteristicmentioning
confidence: 94%
“…Due to the significant regional differences in macrolideresistant (MR) rate, period, patient age and disease type among the studies (Pereyre et al, 2007;Cardinale et al, 2013;Diaz et al, 2015b;Ho et al, 2015;Kogoj et al, 2015), to date there are limited investigations on the distribution of M. pneumoniae types between adult and pediatric populations. Additionally, based on the finding from different regions (Diaz et al, 2015a,b;Ho et al, 2015;Kogoj et al, 2015;Sun et al, 2017;Yan et al, 2015), the correlation between macrolide resistance and M. pneumoniae genotype is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…pneumoniae specimens directly from 480 polymerase chain reaction (PCR)-positive respiratory specimens collected at the Affiliated Children’s Hospital of the Capital Institute of Pediatrics, Beijing, China, between 2003 and 2015. Specimens collected from 2008–2013 (69.0%, 331/480) have been previously reported [6, 7, 9, 10], while specimens collected from 2003–2007(4.8%, 23/480) and 2014–2015 (26.2.%, 126/480) are being described for the first time. M .…”
Section: Methodsmentioning
confidence: 99%
“…pneumoniae genotypes, along with drug resistance profiles, can differ between regions and countries [6, 7]. , and even within the same region, type-shifts in predominant P1 genotypes have been recorded in Japan at intervals of about 10 years [8].…”
Section: Introductionmentioning
confidence: 99%